2014
DOI: 10.5604/20831862.1111435
|View full text |Cite
|
Sign up to set email alerts
|

The COMBINATION OF Α-Lipoic ACID INTAKE WITH ECCENTRIC EXERCISE MODULATES ERYTHROPOIETIN RELEASE

Abstract: The generation of reactive nitrogen/oxygen species (RN/OS) represents an important mechanism in erythropoietin (EPO) expression and skeletal muscle adaptation to physical and metabolic stress. RN/OS generation can be modulated by intense exercise and nutrition supplements such as α-lipoic acid, which demonstrates both anti- and pro-oxidative action. The study was designed to show the changes in the haematological response through the combination of α-lipoic acid intake with running eccentric exercise. Sixteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…To counteract an inflammatory response and oxidative stress, the supplementation of substances with anti-inflammatory and antioxidant capabilities is usually practiced after physical exercise. One of these substance is alpha lipoic acid (ALA) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To counteract an inflammatory response and oxidative stress, the supplementation of substances with anti-inflammatory and antioxidant capabilities is usually practiced after physical exercise. One of these substance is alpha lipoic acid (ALA) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…ALA has different functions in the human metabolism. ALA is part of the multienzyme complex of pyruvate dehydrogenase, alpha-ketoglutarate and branched alpha-keto acids [ 16 18 ]. Additionally, ALA has an antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of reactive nitrogen/oxygen species (RNS/ROS) represents an important mechanism in erythropoietin (EPO) expression and skeletal muscle adaptation to physical and metabolic stress. Morawin et al have shown that the generation of RNS/ROS can be modulated by controlled physical exercise and by taking food supplements such as ALA which has both an anti- and pro-oxidative action [ 82 ]. The study was planned to highlight how the intake of ALA in combination with physical exercise modulated the hematological response.…”
Section: Antioxidant: Sulfur-containing Compoundsmentioning
confidence: 99%
“…BCAA (Branched Chain Amino Acids) is considered by some researchers as both anti-catabolic and anabolic [21]. Other ergogenic aids and/or protective agents used included ubiquinol, acetyl L-carnitine, alpha lipoic acid, and beta-alanine [22][23][24][25][26][27]. A third group of nutrients had Table 1 Daily intake of all nutrients, taken as supplements (see next table) resulting in an 1,300 calories energy-intake per day.…”
Section: Selection Of Nutrientsmentioning
confidence: 99%